1) (3x - 8y)² = (3x)² - 2 * 3x * 8y + (8y)² = 9x² - 48xy + 64y²
2) (7z + 11d)² = (7z)² + 2 * 7z * 11d + (11d)² = 49z² + 154zd + 121d²
3) (3,5t - 4k)² = (3,5t)² - 2 * 3,5t * 4k + (4k)² = 12,25t² - 28tk + 16k²
4) (5k + 1,2t)² = (5k)² + 2 * 5k * 1,2t + (1,2t)² = 25k² + 12kt + 1,44t²
![5)(\frac{2}{3}a-\frac{3}{7}b)^{2}=(\frac{2}{3}a)^{2}-2*\frac{2}{3}a*\frac{3}{7}b+(\frac{3}{7}b)^{2}=\frac{4}{9} a^{2}-\frac{4}{7}ab+\frac{9}{49}b^{2}\\\\6)(\frac{7}{8}c-\frac{4}{7}d)^{2}=(\frac{7}{8}c)^{2}-2*\frac{7}{8}c*\frac{4}{7}d+(\frac{4}{7}d)^{2}=\frac{49}{64}c^{2}-cd+\frac{16}{49}d^{2} 5)(\frac{2}{3}a-\frac{3}{7}b)^{2}=(\frac{2}{3}a)^{2}-2*\frac{2}{3}a*\frac{3}{7}b+(\frac{3}{7}b)^{2}=\frac{4}{9} a^{2}-\frac{4}{7}ab+\frac{9}{49}b^{2}\\\\6)(\frac{7}{8}c-\frac{4}{7}d)^{2}=(\frac{7}{8}c)^{2}-2*\frac{7}{8}c*\frac{4}{7}d+(\frac{4}{7}d)^{2}=\frac{49}{64}c^{2}-cd+\frac{16}{49}d^{2}](https://tex.z-dn.net/?f=5%29%28%5Cfrac%7B2%7D%7B3%7Da-%5Cfrac%7B3%7D%7B7%7Db%29%5E%7B2%7D%3D%28%5Cfrac%7B2%7D%7B3%7Da%29%5E%7B2%7D-2%2A%5Cfrac%7B2%7D%7B3%7Da%2A%5Cfrac%7B3%7D%7B7%7Db%2B%28%5Cfrac%7B3%7D%7B7%7Db%29%5E%7B2%7D%3D%5Cfrac%7B4%7D%7B9%7D%20a%5E%7B2%7D-%5Cfrac%7B4%7D%7B7%7Dab%2B%5Cfrac%7B9%7D%7B49%7Db%5E%7B2%7D%5C%5C%5C%5C6%29%28%5Cfrac%7B7%7D%7B8%7Dc-%5Cfrac%7B4%7D%7B7%7Dd%29%5E%7B2%7D%3D%28%5Cfrac%7B7%7D%7B8%7Dc%29%5E%7B2%7D-2%2A%5Cfrac%7B7%7D%7B8%7Dc%2A%5Cfrac%7B4%7D%7B7%7Dd%2B%28%5Cfrac%7B4%7D%7B7%7Dd%29%5E%7B2%7D%3D%5Cfrac%7B49%7D%7B64%7Dc%5E%7B2%7D-cd%2B%5Cfrac%7B16%7D%7B49%7Dd%5E%7B2%7D)